What Drives Intellectual Capital Disclosure? Evidence from Indonesian Listed Companies - Munawarah Munawarah; Erwin Arianto Lumbantoruan; Simpati Mellyginta Sinuhaji (Jurnal Ekonomi Bisnis Digital, 2026)
Intellectual Capital Disclosure (ICD) has become an essential mechanism for enhancing corporate transparency and providing stakeholders with information about a company’s intangible assets. Despite its increasing importance, the level of intellectual capital disclosure differs across firms and may be influenced by various organisational characteristics. Therefore, this study aims to examine the effects of firm size, profitability, corporate reputation, and leverage on intellectual capital disclosure among non-cyclical consumer companies in the food and beverage subsector listed on the Indonesian Stock Exchange (IDX). This study employed a quantitative research approach using secondary data obtained from the 2024 annual reports of listed companies. The population consisted of 98 companies, and the sample was selected through purposive sampling based on three predetermined criteria, resulting in 59 companies for analysis. Multiple linear regression analysis was used to examine the influence of firm size, profitability, corporate reputation, and leverage on intellectual capital disclosure. The findings reveal that firm size and profitability have a significant positive effect on intellectual capital disclosure, indicating that larger and more profitable firms tend to disclose more comprehensive information regarding their intellectual capital. In contrast, corporate reputation has a negative but statistically insignificant effect, while leverage shows a positive but insignificant effect on intellectual capital disclosure. These findings suggest that company size and profitability are important determinants of intellectual capital disclosure, whereas corporate reputation and leverage do not significantly explain variations in disclosure practices. This study contributes to the growing literature on intellectual capital disclosure by providing empirical evidence from Indonesia’s food and beverage industry and offers practical insights for managers, investors, and policymakers seeking to improve transparency in reporting intellectual capital.